As novas redes sociotécnicas da publicidade em Sergipe: linguagem e comunicação digital - Sá, Suelene Kátia de Souza (2024)
In this dissertation, i propose to analyze the dynamics and transformations of advertising in Sergipe, through an approach that pays attention to the configuration of relational spaces and the networks formed by human and non-human collectives in the context of advertising, based on the interactions between professionals and their audiences, and the participation of objects, artifacts, machines and techniques in the composition of the social and in the establishment of communicative action. In particular, I seek to analyze the intense and tense transformations that advertising has faced in its practices and relationships in recent years, driven by the growing participation of digital and virtual technologies in workspaces and in the mediation between the traditional collectives that make up advertising culture, with political and socio-economic consequences for some actors, always within the capitalist logic of production. To account for these relational dynamics, I use the concept of socio-technical networks in the field of the anthropology of science and technology, and the theoretical and epistemological framework of the Chilean school of the biology of knowing, understanding the formation of social systems as the construction of shared realities in the relational space of language. At the same time, I try to follow the actors, human or not, who participate in the advertising context in Sergipe in the genesis and conservation of these new common landscapes, understanding this study as a contribution to the discussion, within the scope of anthropology, of the specificities of advertising culture, especially in the state of Sergipe.